2019
DOI: 10.4055/cios.2019.11.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Local Recurrence in Giant-Cell Tumor of Bone Treated by Neoadjuvant Denosumab

Abstract: Background Giant-cell tumor of bone (GCTB) is a locally aggressive primary benign tumor presenting as an expansile osteolytic lesion affecting the epiphysis of long bones. Denosumab halts the osteolysis by giant cells thereby downstaging the tumor, helping in performing less morbid procedures to remove the tumor. Our aim was to report the incidence of local recurrence (LR) in patients operated following neoadjuvant denosumab, to investigate factors associated with LR following extended curettage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…However, Chen et al [8] indicated a comparable local recurrence rate between preoperative denosumab followed by curettage and curettage-only group in sacral GCTB (3/11, 27.27% versus 3/10, 30.00%). A definite conclusion has yet to be obtained about preoperative denosumab on the local recurrence of GCTB treated with curettage because of contradictory results across published studies [7][8][9][10][11][12][13][14][15]. The current study is a systematic review and meta-analysis that investigates the effect of preoperative denosumab on the local recurrence of GCTB treated with curettage.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
See 1 more Smart Citation
“…However, Chen et al [8] indicated a comparable local recurrence rate between preoperative denosumab followed by curettage and curettage-only group in sacral GCTB (3/11, 27.27% versus 3/10, 30.00%). A definite conclusion has yet to be obtained about preoperative denosumab on the local recurrence of GCTB treated with curettage because of contradictory results across published studies [7][8][9][10][11][12][13][14][15]. The current study is a systematic review and meta-analysis that investigates the effect of preoperative denosumab on the local recurrence of GCTB treated with curettage.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Previous studies indicated that preoperative denosumab could result in beneficial surgical downstaging in the treatment of GCTB [6]. Data from other studies suggested that preoperative denosumab might increase the risk of local recurrence after the curettage of GCTB [7][8][9][10][11][12][13][14][15]. Scoccianti et al [13] evaluated the local recurrence rate of GCTB treated with curettage and cryotherapy, and the authors observed a higher local recurrence rate in preoperative denosumab plus the…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that these adjuvants, although they possibly facilitate more effective or safe surgery, have limited influence on decreasing the recurrence rate 9 , 18 . Recent studies report that neoadjuvant treatment with denosumab actually increases the risk of recurrence after surgery, making its use for this indication problematic 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Denosumab was approved by the U.S. Food and Drug Administration for use in the treatment of these surgically challenging GCTs in 2013 6 . Since that time it has been tried as a salvage treatment or a neoadjuvant preoperative measure, but recent reviews indicate that it usually results in only partial response and can in fact increase the risk of postoperative recurrence after later curettage 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that denosumab was the only independent factor relevant to local recurrence by multivariate analysis, although the other two factors, the initial type of treatment and the location of the tumor, played roles on univariate analysis. Chinder et al ( 43 ) conducted a study of 123 patients to evaluate the local recurrence of neoadjuvant denosumab following extensive curettage. This study was well-matched for the site of tumor and the type of surgery.…”
Section: Denosumab May Increase the Risk Of Local Recurrence In Patiementioning
confidence: 99%